Exploration of school meal food service management: a case study of a full-day school - Stefania Widya Setyaningtyas; Agnessia Nanda Arimbi; Rian Diana (International Journal of Public Health Science (IJPHS), 2022)
This research was aimed to capture the practice of foodservice management and food acceptance for change unbalance dietary intake children in a fullday Elementary School. School meal food service management is a program for students to improve the nutrition intake An observation form, along with an in-depth interview was used to explore food production practice. Quantitative data on food satisfaction as well as food waste was also measured. Observation in food service management explained that low food acceptance was mainly found in vegetable products. The food quality, especially in taste and texture, became the determinant of the high vegetable food waste. Improving food service management production procedures, including menu planning and evaluation, procurement, preparation, and cooking, could be a promising strategy to increase food acceptance and to reduce food waste.